Expression and purification of 6xHis-tagged DNA binding domains of functional ecdysteroid receptor from Drosophila melanogaster. - Rusin, A.; Niedziela-Majka, A.; Rymarczyk, G.; Ozyhar, A. (Acta Biochimica Polonica, 1996)
Two members of the nuclear receptor superfamily, EcR and Ultraspiracle (Usp) heterodimerize to form a functional receptor for 20-hydroxyecdysone-the key ecdysteroid controlling induction and modulation of morphogenetic events through Drosophila development. In order to study aspects of receptor function and ultimately the structural basis of the ecdysteroid receptor-DNA interaction, it is necessary to produce large quantities of purified EcR and Usp DNA-binding domains. Toward this end, we have expressed the EcR DNA-binding domain and the Usp DNA-binding domain as proteins with an affinity tag consisting of six histidine residues (6xHis-EcRDBD and 6xHis-UspDBD, respectively) using the expression vector pQE-30. Under optimal conditions, elaborated in this study, bacteria can express the recombinant 6xHis-EcRDBD to the levels of 11% of total soluble proteins and the 6xHis-UspDBD to the levels of 16%. Both proteins were purified to homogeneity from the soluble protein fraction using combination of ammonium sulphate fractionation and affinity chromatography on Ni-NTA agarose. The gel mobility shift experiments demonstrated that the purified 6xHis-EcRDBD and the 6xHis-UspDBD interact specifically with an 20-hydroxyecdysone response element from the promoter region of the hsp 27 Drosophila gene.